Pembelajaran Mendalam dalam Pendidikan Pancasila: Arah Baru Pendidikan Bermutu untuk Semua di Sekolah Dasar - Saqjuddin, Saqjuddin; Parisu, Chairan Zibar L; Saputra, Erwin Eka (Journal of Information System and Education Development, 2025)
This study explores the implementation of deep learning approaches in Pancasila Education as a new direction for achieving quality education for all in Indonesian elementary schools. Deep learning in this context emphasizes not only cognitive understanding but also the internalization of values, critical thinking, and character building. By employing a literature-based research design, this study synthesizes recent findings (2019–2024) on how deep learning strategies can transform Pancasila Education into a more meaningful, inclusive, and future-oriented practice. The results indicate that deep learning enhances students’ ability to connect Pancasila values with real-life situations, thereby making learning more contextual and reflective. Moreover, deep learning aligns closely with the goals of the Profil Pelajar Pancasila, which highlights faith, independence, global diversity, collaboration, critical reasoning, and creativity. The integration of digital technology further strengthens the effectiveness of this approach, enabling interactive, project-based, and student-centered learning. Challenges remain, particularly in terms of teachers’ readiness, limited resources, and administrative burdens, which often hinder the full implementation of deep learning practices. Nevertheless, this study concludes that adopting deep learning in Pancasila Education can foster civic literacy, social-emotional competence, and 21st-century skills among students. Therefore, deep learning provides not only a pedagogical strategy but also a paradigm shift in reimagining Pancasila Education as a transformative force for achieving inclusive and high-quality education for all.